2016
DOI: 10.1093/mnras/stw1915
|View full text |Cite
|
Sign up to set email alerts
|

TheSwift-BAT monitoring reveals a long-term decay of the cyclotron line energy in Vela X-1

Abstract: We study the behaviour of the cyclotron resonant scattering feature (CRSF) of the high mass X-ray binary Vela X-1 using the long-term hard X-ray monitoring performed by the Burst Alert Telescope (BAT) on board Swift. High statistics, intensity selected spectra were built along 11 years of BAT survey. While the fundamental line is not revealed, the second harmonic of the CRSF can be clearly detected in all the spectra, at an energy varying between ∼ 53 keV and ∼ 58 keV, directly correlated with the luminosity. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
0
22
1
Order By: Relevance
“…3.1.5) as the fundamental cyclotron line, we can use Eq. (7) to infer a magnetic field strength in the line-forming region of 2 × (1 + z)10 12 G. As has been shown by Fürst et al (2010) and La Parola et al (2016), the first harmonic (at about 55 keV) shows a correlation with luminosity, indicating that the line-forming region changes in altitude above the surface of the neutron star. Using this correlation and theoretical calculations by Becker et al (2012) and Fürst et al (2010) inferred a surface magnetic field of B = 2.6 × 10 12 G. However, this value should be taken only as an estimate because it depends on the exact physical conditions within the accretion column, in particular, on the dominating process of decelerating the in-falling material, as well as on the mass and radius of the neutron star.…”
Section: Strength Of the Magnetic Field Of The Neutron Starmentioning
confidence: 60%
See 1 more Smart Citation
“…3.1.5) as the fundamental cyclotron line, we can use Eq. (7) to infer a magnetic field strength in the line-forming region of 2 × (1 + z)10 12 G. As has been shown by Fürst et al (2010) and La Parola et al (2016), the first harmonic (at about 55 keV) shows a correlation with luminosity, indicating that the line-forming region changes in altitude above the surface of the neutron star. Using this correlation and theoretical calculations by Becker et al (2012) and Fürst et al (2010) inferred a surface magnetic field of B = 2.6 × 10 12 G. However, this value should be taken only as an estimate because it depends on the exact physical conditions within the accretion column, in particular, on the dominating process of decelerating the in-falling material, as well as on the mass and radius of the neutron star.…”
Section: Strength Of the Magnetic Field Of The Neutron Starmentioning
confidence: 60%
“…Fürst et al (2014) found a positive correlation of the harmonic (higher-energy) line with flux, as expected for a source in the subcritical accretion regime as defined by Becker et al (2012). La Parola et al (2016) undertook a long-term study of Swift/BAT data of Vela X-1. While the fundamental line was not evident in their 15-150 keV spectra, the first harmonic of the CRSF was clearly detected between ∼53 and ∼58 keV, and with an apparent positive correlation of the line energy with luminosity, flattening above L 1−150 keV ≈ 5 × 10 36 erg s −1 .…”
Section: Cyclotron Resonance Scattering Featuresmentioning
confidence: 67%
“…The red line is a fit to these two data sets defining σ = 0.18 E cyc . The individual sources are GX 304−1 (Klochkov et al 2015), Swift J1626.6−5156 (DeCesar et al 2013, Vela X-1 (La Parola et al 2016), and Her X-1 (same as Fig. 4).…”
Section: Changes In E Cyc With Fluxmentioning
confidence: 96%
“…In this time window the source is detected in the 60-110 keV band at 3.5 σ . Finally, we also associated to this spectrum a systematic error of the order of 2 per cent using deviations from the Crab spectrum (see La Parola et al 2016).…”
Section: Spectral Analysis Of the Single Datasetsmentioning
confidence: 99%